2004
DOI: 10.1083/jcb.200405013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative kinetic analysis of nucleolar breakdown and reassembly during mitosis in live human cells

Abstract: One of the great mysteries of the nucleolus surrounds its disappearance during mitosis and subsequent reassembly at late mitosis. Here, the relative dynamics of nucleolar disassembly and reformation were dissected using quantitative 4D microscopy with fluorescent protein-tagged proteins in human stable cell lines. The data provide a novel insight into the fates of the three distinct nucleolar subcompartments and their associated protein machineries in a single dividing cell. Before the onset of nuclear envelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 39 publications
4
133
0
1
Order By: Relevance
“…2,31 Interestingly, we found that after aclarubicin treatment a small number of early antephase cells proceed to the end of antephase where they arrested for hours with disassembled nucleoli (Mikhailov, Shinohara and Rieder, unpublished observations). This suggests that in these cells, there is sufficient CDK2 activity to drive chromatin condensation and nucleoli dispersion, 50 but not enough cyclin B/CDK1 activity to induce NEB. This could occur, e.g., if the activity of the Cdc25B phosphatase was limited.…”
Section: How Does the P38 Checkpoint Inhibit Progression Through Antementioning
confidence: 99%
“…2,31 Interestingly, we found that after aclarubicin treatment a small number of early antephase cells proceed to the end of antephase where they arrested for hours with disassembled nucleoli (Mikhailov, Shinohara and Rieder, unpublished observations). This suggests that in these cells, there is sufficient CDK2 activity to drive chromatin condensation and nucleoli dispersion, 50 but not enough cyclin B/CDK1 activity to induce NEB. This could occur, e.g., if the activity of the Cdc25B phosphatase was limited.…”
Section: How Does the P38 Checkpoint Inhibit Progression Through Antementioning
confidence: 99%
“…In prophase, these nucleoli disassemble and their transcription becomes repressed to allow the stripped rDNA to segregate with the rest of the genome. Nucleolar transcription is downregulated by the CDK1-cyclin B kinase, whose phosphorylation of promoter selectivity factor SL1 prevents the formation of the PolI pre-initiation complex [63][64][65] . Similar to yeast Rio1, RIOK1 might just as well contribute to the transcriptional repression of PolI.…”
Section: Discussionmentioning
confidence: 99%
“…HeLa and HeLa(E-GFP-Ago2) cell lines were generated as described previously (29) and grown with the supplement of 600 g/ml G418 for selection. Dicerϩ/Ϫ, DicerϪ/Ϫ (J.M.C.…”
Section: Methodsmentioning
confidence: 99%